Error Correction Decoding Algorithms of RS Codes Based on an Earlier Termination Algorithm to Find the Error Locator Polynomial - Jiang, Zhengyi; Shi, Hao; Huang, Zhongyi; Song, Linqi; Bai, Bo; Zhang, Gong; Hou, Hanxu (IEEE transactions on information theory, 2025)
Reed-Solomon (RS) codes are widely used to correct errors in storage systems. Finding the error locator polynomial is one of the key steps in the error correction procedure of RS codes. Modular Approach (MA) is an effective algorithm for solving the Welch-Berlekamp (WB) key-equation problem to find the error locator polynomial that needs 2t steps, where t is the error correction capability. In this paper, we first present a new MA algorithm that only requires 2e steps and then propose two fast decoding algorithms for RS codes based on our MA algorithm, where e is the number of errors and e≤ t . We propose the Improved-Frequency Domain Modular Approach (I-FDMA) algorithm that needs 2e steps to solve the error locator polynomial and present our first decoding algorithm based on the I-FDMA algorithm. We show that, compared with the existing methods based on MA algorithms, our I-FDMA algorithm can effectively reduce the decoding complexity of RS codes when e\lt t . Furthermore, we propose the t_{0} -Shortened I-FDMA ( t_{0} -SI-FDMA) algorithm ( t_{0} is a predetermined even number less than 2t-1 ) based on the new termination mechanism to solve the error number e quickly. We propose our second decoding algorithm based on the SI-FDMA algorithm for RS codes and show that the multiplication complexity of our second decoding algorithm is lower than our first decoding algorithm (the I-FDMA decoding algorithm) when 2e\lt t_{0}+1 .